PENGARUH SERTIFIKASI HALAL TERHADAP NIAT BELANJA GENERASI MILENIAL KABUPATEN ROKAN HULU - Andi Lesmana; Martiana (Jurnal Bina Wira, 2024)
This study aims to determine the effect of halal certification on millennial generation shopping intentions for Rokan Hulu specialty food products. The sample of this study consisted of 100 millennial generation respondents aged between 25-45 years in the Rokan Hulu area, randomly selected using convenience sampling technique. Data was collected through a questionnaire that focused on perceptions of product halalness and shopping intentions. Data analysis was carried out using multiple linear regression methods with the help of SPSS version 25 software. The results showed a significant positive relationship between halal certification and millennial generation shopping intentions for Rokan Hulu specialty food products (p < 0.05). The managerial implication of this research is the importance of maintaining or obtaining halal certification to increase product attractiveness among the millennial generation, as well as improving marketing strategies that focus on product halalness to support increased sales and consumer loyalty.